PENGARUH MODEL CONNECTED MATHEMATICS PROJECT TERHADAP KEMAMPUAN KONEKSI MATEMATIS DAN SELF-EFFICACY SISWA SEKOLAH DASAR - Akbar, Moch Rizkia; Irawati, Riana; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2019)
This research is motivated by the lack of mathematical connection skills of students, mathematical connection ability is one of the skills that must be possessed by students in learning mathematics. In learning also students need to have self-efficacy to increase self-confidence in learning. Learning by using the connected mathematics project model is one option that can be used to improve students' mathematical connection skills and self-efficacy. The purpose of this study was to determine the increase in mathematical connection ability and self-efficacy of students using the connected mathematics project model, to determine the differences in mathematical connection abilities and student self-efficacy in the experimental and control classes, and to determine the relationship between mathematical connection ability and focus-efficacy. The research method in this study is a quasi experimental with nonequivalent control group design. The population used is the 4th grade students of elementary school in Kertasemaya District. While the sample used was the 4th grade students of SDN 1 Tulungagung as the experimental class and Kertasemaya 1 Elementary School as the control class. After conducting research for three meetings, mathematical connection ability and self-efficacy in both classes increased. The increase in mathematical connection ability in the experimental class is better than the control class, while self-efficacy in the control class has improved better than the experimental class. Even though both of them experienced an increase, there was no significant difference between the two classes, between mathematical connection ability and self-efficacy also had no relationship. Thus, it can be seen that the connected mathematics project model and conventional models have a positive influence on students' mathematical connection skills and self-efficacy.